Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - 2.2 - Addition and Subtraction of Rational Numbers - Problem Set 2.2 - Page 58: 79



Work Step by Step

We first apply the distributive property. Then, we simplify the resultant expression: $\frac{7}{13}(\frac{2}{3}-\frac{1}{6})$ =$\frac{7}{13}(\frac{2}{3})-\frac{7}{13}(\frac{1}{6})$ =$\frac{7\times2}{13\times3}-\frac{7\times1}{13\times6}$ =$\frac{14}{39}-\frac{7}{78}$ =$\frac{2(14)-7(1)}{78}$ =$\frac{28-7}{78}$ =$\frac{21}{78}$ =$\frac{7}{26}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.